Formation of the motivational and value component of future border guard officers’ readiness for physical education of personnel - Melnykov, A.; Rybak, L. (Journal of Education, Health and Sport, 2017)
The data on the state of motivational and value component of the readiness of future border guard officers to physical education of personnel was obtained and analyzed. The state of formation of such readiness was determined using the methodology of T. Ehlers, but adapted to the characteristics of the investigated contingent. It was represented by 128 cadets of the specialized institution of higher education. The state of formation in them of such readiness was determined using the methodology of T. Ehlers, but language adapted to the characteristics of the investigated contingent. There were 128 cadets of the specialized institution of higher education, and the main criterion was the formation of an internal type of motivation for implementation at a high methodological level of physical education of the personnel. It was determined that the expected result was reached by 70.3% of the cadets, the grades of the rest were slightly lower. The obtained data indicated a reserve for improvement, first of all, regarding the approaches to formation and implementation of the content of physical training of future officers of the Border Guard Service during their study in a specialized institution of higher education. This will increase the number of graduates with high and higher than the average levels of motivational and value readiness for the physical education of personnel.